Magnetic nano-particles as well as preparation method and application thereof

Through the design of Fe3O4@PDA@cDNA magnetic nanoparticles, using PDA as the connecting layer to fix DNA molecules, the problems of sequence selectivity and non-specific adsorption during DNA extraction in the prior art were solved, and efficient and stable DNA hybridization and extraction effects were achieved.

CN119633739APending Publication Date: 2025-03-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311190830.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

It is difficult for existing magnetic nanoparticles to achieve high sequence selectivity and low non-specific adsorption during DNA extraction, and DNA molecules are not fixed firmly and are easily replaced by other molecules.

Method used

Fe3O4@PDA@cDNA magnetic nanoparticles are used, which are composed of Fe3O4 magnetic nanoparticles, polydopamine (PDA) and covalently modified DNA (cDNA). Using PDA as the linking layer, DNA molecules are fixed by Michael addition or Schiff base reaction.

Benefits of technology

It achieves high sequence selectivity, low non-specific adsorption, high DNA hybridization capacity, high chemical stability, good water dispersion, renewable and reusable effects, and can maintain high hybrid capacity and selectivity in complex environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633739A_ABST
    Figure CN119633739A_ABST
Patent Text Reader

Abstract

The invention discloses magnetic nanoparticles as well as a preparation method and application thereof, and belongs to the technical field of preparation of magnetic nano materials. The magnetic nanoparticles provided by the invention are Fe3O4 (at) PDA (at) cDNA (complementary deoxyribonucleic acid); the magnetic nanoparticles comprise ferroferric oxide (at) PDA (Personal Digital Assistant) core-shell nanoparticles and cDNA (Complementary Deoxyribonucleic Acid), the ferroferric oxide (at) PDA core-shell nanoparticles comprise ferroferric oxide magnetic nanoparticles and polydopamine; the ferroferric oxide magnetic nanoparticles are coated with the polydopamine; the cDNA is connected to the surface of the ferroferric oxide (at) PDA core-shell nanoparticle. The magnetic nanoparticles provided by the invention have the advantages of high sequence selectivity, low non-specific adsorption, high DNA hybridization capacity, high chemical stability, good water dispersibility, reproducibility, reusability, complex environment interference resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of preparation of magnetic nanomaterials, and in particular to a magnetic nanoparticle and a preparation method and application thereof. Background Art

[0002] Magnetic particles are widely used in the separation, purification, enrichment and detection of targets, and have the advantages of being easy and fast to operate. For DNA extraction, some magnetic particles are designed to achieve high loading capacity and high DNA purity, and often do not have sequence selectivity, such as silica-coated magnetic particles (Fe 3 O 4 @SiO 2 ). However, in some cases, it is necessary to selectively extract target DNA molecules of a specific sequence. In this case, the complementary base pairing principle can be used to covalently modify the complementary sequence on the surface of the magnetic particles.

[0003] The commonly used strategy for fixing complementary DNA molecules on the surface of magnetic particles is to firstly utilize tetraethoxysilane (TEOS) hydrolysis and polycondensation reaction on Fe 3 O 4 The surface of the magnetic particles is coated with a layer of silica, and then amino groups are introduced through aminopropyltriethoxysilane (APTES), and then glutaraldehyde is used as a coupling agent to fix the amino-modified DNA molecules or connect the carboxyl-modified DNA molecules through EDC / NHS reaction. In addition, a layer of gold film can be coated on the surface of the magnetic particles first, and then the thiol-modified DNA molecules are fixed through Au-S bonds. Of the above two methods, the former has cumbersome steps, and the amino surface is very likely to have strong nonspecific adsorption on DNA molecules; while the latter connects DNA molecules that are not firmly connected and are easily replaced by other thiol-containing molecules.

[0004] The surface modification method of polydopamine (PDA) is simple to operate, has mild conditions, and has a wide range of applications. The object to be modified is immersed in a weak alkaline solution containing dopamine. Dopamine uses the dissolved oxygen in the solution to undergo self-oxidative polymerization and is deposited on the surface of the object to be modified to form a layer of polydopamine coating. This method is applicable to the surface modification of almost any material, and PDA can fix molecules containing amino or thiol groups through Michael addition or Schiff base reaction. However, since both PDA and DNA molecules are negatively charged, electrostatic repulsion makes it difficult for DNA molecules to approach the PDA surface to react, so the reaction efficiency is usually very low. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a magnetic nanoparticle and a preparation method and application thereof. The magnetic nanoparticle has the advantages of high sequence selectivity, low nonspecific adsorption, high DNA hybridization capacity, high chemical stability, good water dispersibility, renewability, reusability and resistance to complex environmental interference.

[0006] In order to achieve the above-mentioned invention object, this application provides the following technical solutions:

[0007] On the one hand, the present application provides a magnetic nanoparticle, wherein the magnetic nanoparticle is Fe 3 O 4 @PDA@cDNA;

[0008] The Fe 3 O 4 @PDA@cDNA includes Fe 3 O 4 @PDA core-shell nanoparticles and cDNA;

[0009] The Fe 3 O 4 @PDA core-shell nanoparticles include Fe 3 O 4 Magnetic nanoparticles and polydopamine;

[0010] The polydopamine coated Fe 3 O 4 Magnetic nanoparticles;

[0011] The cDNA is linked to the Fe 3 O 4 @Surface of PDA core-shell nanoparticles.

[0012] Optionally, the coating thickness of the polydopamine is 20 to 40 nm.

[0013] Optionally, one end of the cDNA is modified with an amino group or a thiol group.

[0014] Optionally, the linkage is covalent.

[0015] Optionally, the connection uses the polydopamine as a connection layer.

[0016] In a second aspect, the present application provides a method for preparing the above-mentioned magnetic nanoparticles, comprising the following steps:

[0017] (1) A mixture containing ferric chloride, trisodium citrate, sodium acetate, and ethylene glycol is reacted to obtain Fe 3 O 4 Magnetic nanoparticles;

[0018] (2) The Fe3 O 4 A mixture of magnetic nanoparticles and dopamine hydrochloride is reacted to obtain Fe 3 O 4 @PDA core-shell nanoparticles;

[0019] (3) The Fe 3 O 4 A mixture of PDA core-shell nanoparticles, metal ions, and cDNA was reacted to obtain Fe 3 O 4 @PDA@cDNA is the magnetic nanoparticle.

[0020] Optionally, the metal ions in step (3) include Mg 2+ and / or Ca 2+ .

[0021] Optionally, the molar concentration of the metal ion in step (3) is 2 to 20 mM.

[0022] Optionally, the Fe in step (3) 3 O 4 @The mixing ratio of PDA core-shell nanoparticles, metal ions, and cDNA is 0.5-2.5 mg / mL: 2-20 mM: 1-5 μM.

[0023] Optionally, the reaction in step (3) comprises a Michael addition reaction or a Schiff base reaction.

[0024] Optionally, the reaction time in step (3) is 2 to 24 hours.

[0025] Optionally, the mixing ratio of ferric chloride, trisodium citrate, sodium acetate and ethylene glycol in step (1) is 1-2 g: 0.1-0.5 g: 1-2 g: 10-30 mL.

[0026] Optionally, the reaction temperature in step (1) is 190-220°C;

[0027] The reaction time is 5 to 15 hours.

[0028] Optionally, the Fe in step (2) 3 O 4 The mixing mass ratio of the magnetic nanoparticles to dopamine hydrochloride is 1-5:5-10.

[0029] Optionally, the reaction in step (2) is a spontaneous oxidation polymerization of dopamine to form polydopamine coated on Fe 3 O 4 Surface of magnetic nanoparticles.

[0030] Optionally, the pH of the reaction in step (2) is 7.5 to 9.5.

[0031] Preferably, the pH of the reaction in step (2) is 8.5.

[0032] Optionally, the reaction time in step (2) is 5 to 10 hours.

[0033] In a third aspect, the present application also provides the use of the above-mentioned magnetic nanoparticles in the separation, purification or detection of target objects.

[0034] Optionally, after hybridizing with the target DNA molecules, the magnetic nanoparticles are heated in a low ionic strength solution to regenerate them.

[0035] Preferably, after hybridization with the target DNA molecule, the magnetic nanoparticles are heated at 50° C. for 10 min in a 10 mM Tris-HCl buffer at pH 8.5 to regenerate them.

[0036] Compared with the prior art, this application has the following beneficial effects:

[0037] (1) The magnetic nanoparticles provided by the present application, the complementary DNA molecules in Ca 2+ or Mg 2+ Induced high density covalent bonding in Fe 3 O 4 @PDA core-shell nanoparticle surface can be used for high-capacity and high-selectivity extraction of target DNA molecules, with minimal adsorption of non-target DNA.

[0038] (2) The magnetic nanoparticles provided in the present application, with complementary DNA molecules fixed by PDA as the connecting layer, have high chemical stability.

[0039] (3) The magnetic nanoparticles provided in the present application can be reused and can be regenerated by heating in a low ionic strength solution after hybridization with the target DNA molecule. The magnetic nanoparticles provided in the present application still retain high hybridization capacity and high sequence selectivity for the target DNA molecule in a complex environment.

[0040] (4) In the process of preparing magnetic nanoparticles in this application, the metal ion Ca is added 2+ or Mg 2+ It can induce cDNA to adsorb on the PDA surface, thereby greatly improving the reaction efficiency and further increasing the Fe 3 O 4 Hybridization capacity of @PDA@cDNA magnetic particles for target DNA molecules. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1In the embodiment of this application, Fe 3 O 4 TEM image of magnetic nanoparticles;

[0042] Figure 2 In the embodiment of this application, Fe 3 O 4 @TEM image of PDA core-shell nanoparticles;

[0043] Figure 3 In the embodiment of this application, Fe 3 O 4 High sequence selectivity and low nonspecific adsorption of @PDA@cDNA magnetic nanoparticles (Note: The target DNA molecule (50nM) is adsorbed with Fe 3 O 4 @PDA, Fe 3 O 4 @PDA@cDNA or Fe 3 O 4 @PDA@ncDNA three kinds of magnetic nanoparticles (0.1mg / mL) were co-incubated, and the fluorescence spectrum of the solution after magnetic separation to remove the bound target DNA);

[0044] Figure 4 In the embodiment of this application, Fe 3 O 4 High DNA hybridization capacity of @PDA@cDNA magnetic nanoparticles (Note: Fe 3 O 4 The amount of target DNA molecules bound after incubation of @PDA@cDNA magnetic nanoparticles (0.1 mg / mL) with target DNA molecules of different concentrations);

[0045] Figure 5 In the embodiment of this application, Fe 3 O 4 High chemical stability of @PDA@cDNA magnetic nanoparticles (Note: Fe 3 O 4 @PDA@cDNA magnetic nanoparticles (0.1 mg / mL) binding percentage to target DNA molecules (50 nM) after being stored in a 4°C refrigerator for different days);

[0046] Figure 6 In the embodiment of this application, Fe 3 O 4 Reusability of @PDA@cDNA magnetic nanoparticles (Note: Fe 3 O 4 @PDA@cDNA magnetic nanoparticles (0.1 mg / mL) and target DNA molecules (50 nM) were repeatedly bound / dissociated for 5 times (binding percentage and dissociation percentage);

[0047] Figure 7 In the embodiment of this application, Fe 3 O 4 @PDA@cDNA magnetic nanoparticles' ability to resist interference from complex environments (Note: Fe 3 O 4 @PDA@cDNA magnetic nanoparticles (0.1 mg / mL) and target DNA molecules (50 nM) in solutions with a BSA content (w / w) of 0-1%. DETAILED DESCRIPTION

[0048] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.

[0049] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.

[0050] Unless otherwise specified, the analysis methods in the examples all adopt conventional settings and conventional analysis methods of instruments or equipment.

[0051] Example 1

[0052] Fe 3 O 4 Preparation of @PDA@cDNA magnetic nanoparticles:

[0053] (1)Fe 3 O 4 Preparation of magnetic nanoparticles:

[0054] Ferric chloride hexahydrate (1.08 g), trisodium citrate dihydrate (0.40 g) and anhydrous sodium acetate (1.20 g) were dissolved in 20 mL of ethylene glycol under vigorous stirring. The reaction mixture was transferred to a stainless steel reactor lined with polytetrafluoroethylene and heated at 200°C for 10 h. After cooling to room temperature, the obtained Fe 3 O 4 The magnetic nanoparticles were washed several times with ethanol and water and dried in vacuum. 3 O 4 TEM electron microscope image Figure 1 As shown, the average particle size is about 122 nm.

[0055] (2)Fe 3 O 4@ Preparation of PDA core-shell nanoparticles:

[0056] 3mg Fe 3 O 4 The magnetic nanoparticles were ultrasonically dispersed in 24 mL Tris-HCl buffer (10 mM, pH 8.5), 7 mg dopamine hydrochloride was added, and the reaction was shaken for 5 h to obtain Fe 3 O 4 @PDA core-shell nanoparticles. Washed several times with water and redispersed in 3 mL Tris-HCl (10 mM, pH 8.5) to obtain Fe 3 O 4 @PDA stock solution (recorded as 1 mg / mL). Fe 3 O 4 @PDA TEM electron microscope image Figure 2 As shown, the thickness of the polydopamine coating is about 30 nm.

[0057] (3)Mg 2+ Induced covalent modification of complementary DNA molecules:

[0058] Take 1 mL Fe 3 O 4 @PDA stock solution, after magnetic separation, was redispersed in 1 mL containing 20 mM MgCl 2 and 2 μM complementary DNA (denoted as cDNA, the nucleotide sequence is shown in SEQ ID NO.1: 5'-3' NH 2 -C 6 -TGT CCG ATG CTC CCT) buffer (10mM Tris-HCl, pH8.5, 150mM NaCl) was shaken at room temperature for 10h. The magnetic particles were collected and washed three times with TE solution (10mMTris-HCl, pH8.5, 5mM EDTA) to remove Mg 2+ The cDNA molecules adsorbed on the surface of magnetic particles but not reacted under induction are Fe 3 O 4 @PDA@cDNA magnetic nanoparticles were dispersed in 1 mL Tris-HCl buffer (10 mM, pH 8.5), recorded as 1 mg / mL, and stored at 4°C for later use.

[0059] Example 2

[0060] Example 1 Preparation of Fe 3 O 4 Research on the properties of @PDA@cDNA magnetic nanoparticles:

[0061] (1) High sequence selectivity and low nonspecific adsorption:

[0062] The Fe prepared in Example 1 3 O 4 @PDA@cDNA magnetic nanoparticles (0.1 mg / mL) were co-incubated with the target DNA molecule (nucleotide sequence as shown in SEQ ID NO.2: 5'-3' GAT CGG GTG TGG GTG GCG TAA AGG GAG CAT CGGACA-FAM, 50 nM). 3 O 4 @PDA@cDNA is immobilized on complementary DNA. To measure the hybridization, the 3' end of the target DNA molecule is labeled with a fluorophore FAM. After a period of time, the target DNA molecules bound to the magnetic particles are removed by magnetic separation, and the fluorescence of the solution is measured to quantify the hybridization of the target DNA molecules. As a control, a non-complementary DNA molecule (nucleotide sequence as shown in SEQ ID NO.3: NH 2 -C 6 -AGG GAG CATCGG ACA) modified magnetic nanoparticles (Fe 3 O 4 @PDA@ncDNA). The target DNA molecule and Fe 3 O 4 @PDA and Fe 3 O 4 @PDA@ncDNA binding status.

[0063] The results are as follows Figure 3 As shown. Figure 3 It can be seen that with Fe 3 O 4 After incubation with @PDA@cDNA, the fluorescence of the solution decreased significantly, while 3 O 4 @PDA or Fe 3 O 4 The fluorescence of the solution decreased slightly after incubation with @PDA@ncDNA, indicating that more target DNA molecules bound to the Fe 3 O 4 @PDA@cDNA particles, it was demonstrated that Fe 3 O 4 High sequence selectivity and low nonspecific adsorption of @PDA@cDNA magnetic nanoparticles.

[0064] (2) High DNA hybridization capacity:

[0065] Fe 3 O 4@PDA@cDNA magnetic nanoparticles (0.1 mg / mL) were incubated with target DNA molecules of different concentrations. After 20 minutes, the target DNA molecules bound to the particles were removed by magnetic separation, and the maximum hybridization amount of the magnetic particles was obtained by measuring the fluorescence of the solution.

[0066] The results are as follows Figure 4 As shown. Figure 4 It can be seen that as the concentration of target DNA molecules increases, the number of target DNA molecules bound to the magnetic particles gradually increases. 3 O 4 @PDA@cDNA magnetic particles, the maximum hybridization amount is about 50nM.

[0067] (3) High chemical stability:

[0068] Fe 3 O 4 The @PDA@cDNA magnetic nanoparticles were stored in a 4°C refrigerator for 10 days, during which some of them were taken out at different days to test their hybridization with the target DNA molecules, using the same method as above.

[0069] The results are as follows Figure 5 As shown. Figure 5 It can be seen that after 10 days of storage, Fe 3 O 4 The hybridization ability of @PDA@cDNA hardly decreased, indicating that the complementary DNA immobilized by this method has high chemical stability.

[0070] (4) Reusability:

[0071] Due to the reversibility of DNA denaturation-renaturation, magnetic nanoparticles bound to target DNA molecules can be regenerated under heating conditions. The regeneration method is: 3 O 4 The complex of @PDA@cDNA and the target DNA molecule was dispersed in a low ionic strength solution (10mM Tris-HCl, pH8.5) and heated at 50°C for 10 minutes. The regenerated magnetic particles still retained a high hybridization capacity for the target DNA molecule. Figure 6 Fe 3 O 4 @PDA@cDNA magnetic nanoparticles were reused 5 times, and the binding percentage with the target DNA molecules and the dissociation percentage of the target DNA molecules during regeneration were calculated each time.

[0072] (5) Anti-interference from complex environments:

[0073] Bovine serum albumin (BSA) was used to simulate a complex environment to study the Fe 3 O 4Hybridization of @PDA@cDNA magnetic nanoparticles with target DNA molecules in solutions with different BSA contents.

[0074] The results are as follows Figure 7 As shown. Figure 7 It can be seen that 1% BSA has a significant effect on Fe 3 O 4 @PDA@ has no effect on the hybridization of cDNA with the target DNA molecule.

[0075] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A magnetic nanoparticle, characterized in that: The magnetic nanoparticles are Fe3O4@PDA@cDNA; The Fe3O4@PDA@cDNA comprises Fe3O4@PDA core-shell nanoparticles and cDNA; The Fe3O4@PDA core-shell nanoparticles include Fe3O4 magnetic nanoparticles and polydopamine; The polydopamine coats the Fe3O4 magnetic nanoparticles; The cDNA is connected to the surface of the Fe3O4@PDA core-shell nanoparticles.

2. The magnetic nanoparticle according to claim 1, characterized in that: The coating thickness of the polydopamine is 20 to 40 nm.

3. The magnetic nanoparticle according to claim 1, characterized in that: One end of the cDNA is modified with an amino group or a thiol group.

4. The magnetic nanoparticle according to claim 1, characterized in that: The connection is a covalent connection; Preferably, the connection uses the polydopamine as a connection layer.

5. The method for preparing magnetic nanoparticles according to any one of claims 1 to 4, characterized in that: The steps include: (1) reacting a mixture containing ferric chloride, trisodium citrate, sodium acetate, and ethylene glycol to obtain Fe3O4 magnetic nanoparticles; (2) reacting a mixture containing the Fe3O4 magnetic nanoparticles and dopamine hydrochloride to obtain Fe3O4@PDA core-shell nanoparticles; (3) reacting a mixture containing the Fe3O4@PDA core-shell nanoparticles, metal ions, and cDNA to obtain Fe3O4@PDA@cDNA, which is the magnetic nanoparticles.

6. The method for preparing magnetic nanoparticles according to claim 5, characterized in that: The metal ions in step (3) include Mg 2+ and / or Ca 2+ ; Preferably, the molar concentration of the metal ion in step (3) is 2 to 20 mM; Preferably, the mixing ratio of the Fe3O4@PDA core-shell nanoparticles, metal ions, and cDNA in step (3) is 0.5-2.5 mg / mL: 2-20 mM: 1-5 μM; Preferably, the reaction in step (3) comprises a Michael addition reaction or a Schiff base reaction; Preferably, the reaction time in step (3) is 2 to 24 hours.

7. The method for preparing magnetic nanoparticles according to claim 5, characterized in that: The mixing ratio of ferric chloride, trisodium citrate, sodium acetate and ethylene glycol in step (1) is 1-2 g: 0.1-0.5 g: 1-2 g: 10-30 mL; Preferably, the reaction temperature in step (1) is 190-220°C; The reaction time is 5 to 15 hours.

8. The method for preparing magnetic nanoparticles according to claim 5, characterized in that: The mixing mass ratio of the Fe3O4 magnetic nanoparticles to dopamine hydrochloride in step (2) is 1-5:5-10.

9. The method for preparing magnetic nanoparticles according to claim 5, characterized in that: The reaction in step (2) is the spontaneous oxidation polymerization of dopamine to form polydopamine coated on the surface of Fe3O4 magnetic nanoparticles; Preferably, the pH of the reaction in step (2) is 7.5 to 9.5; Preferably, the reaction time in step (2) is 5 to 10 hours.

10. Use of the magnetic nanoparticles according to any one of claims 1 to 4 or the magnetic nanoparticles prepared by the preparation method according to any one of claims 5 to 9 in the separation, purification or detection of a target.

Citation Information

Patent Citations

  • Polydopamine nanosphere biosensor

    CN103884838A

  • Method for grafting DNA on polydopamine nanoparticle surface with controllable density

    CN109369912A

  • Preparation method and application of polydopamine-modified magnetic nanoparticle

    CN110142035A

  • Aptamer sensor for self-assembly of DNA hydrogel based on rolling circle amplification product and application of aptamer sensor

    CN113189323A

  • Method for improving covalent modification quantity of DNA (deoxyribonucleic acid) molecules on surface of polydopamine

    CN118086456A